Менеджмент консалтинговой организацией: особенности маркетинга и PR - Королько, В.; Некрасова, О. (Социология: теория, методы, маркетинг, 2004)
Taking into account the exciting growth of consulting industry throughout the world in
recent years (Ukraine including) as well as rapid increase of competition in the sphere
of intangible services the authors attempt to analyze the unique challenges for
marketing and communications facing the professional consulting companies and
firms. They emphasize that their goals can be met only through a strategic, integrated
approach to marketing and PR communications. To be effective such an approach
must support and reflect the consulting organizations overall mission and goals,
consistent branding and positioning strategies, and also relevant marketing tactics
that include: effective message development, internal communication programs,
image advertising, media relations/external communications, and group oriented
special events and activities.